Kejujuran dalam Perspektif Pendidikan Islam: Nilai Fundamental, Strategi Implementasi, dan Dampaknya terhadap Pembentukan Karakter Santri di Pesantren - Suci Ramadani; Ainur Rofiq Sofa (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Honesty is one of the core values in Islamic education that serves as a foundation for shaping individual character, particularly in Islamic boarding schools (pesantren). This study aims to explore honesty as a fundamental value in Islam, its implementation strategies in pesantren, and its impact on the character development of students (santri). Using a qualitative approach, this research utilizes literature analysis and field observations to understand how honesty is taught, practiced, and internalized in the daily lives of students. The findings reveal that honesty is implemented through the reinforcement of religious values in daily activities, fostering truthful behavior in the teaching-learning process, and role modeling by caregivers and educators. Implementation strategies include an ethics-based educational approach, strict supervision, and continuous evaluation. The impact is evident in the increased self-confidence of students, strengthened integrity, and their ability to face life challenges in alignment with Islamic principles. Thus, honesty is not only a critical element in shaping the character of students but also a foundation for developing individuals who are responsible, trustworthy, and morally upright. This study recommends the consistent application of honesty-based learning methods as a pillar of character education in pesantren.